Medicinal and Social Importance of Trees Mentioned in Punjabi Folk Songs - Batool, Saima; Sarfraz, Mariam; Sozaina Younus, Sidra (sourcecoder, 2022)
We should observe the medicinal, geographical, economical, historical and social conditions of any region to understand the specialties of folk songs. As we know that the literature of any area, nation, country and language is emanated from its envoirment. For example the inhabitants of deserts would express deserts, way farer, camels, rocks, sand, scarcity of water and abandoned area in their folk songs. Moreover the people who are residing near the rivers, oceans, canals would mention water, waves, storms, ships, boats in their song. Similarly the people of agricultural areas like Punjab describe crops, fruits, gardens, vegetables, flowers, lakes, seasons, spices and trees in their poetry and songs. In this research article it has been tried to describe the trees mentioned in folk songs which are useful for society in various aspects.